Two new diverse 3D MOFs induced by ligand salt type: Photocatalytic performance. (March 2021) - Wang, Jun; Rao, Congying; Zhou, Shanhe; Hu, Wuxin; Wang, Jing; Lu, Lu; Mai, Yanhong; Pan, Ying; Cheng, Fan; Muddassir, Mohd.
Abstract: Self-assembly of Zn(Ac)2 ·2H2 O with π-conjugated and rigid multicarboxylate ligand 1, 3, 5-benzenetricarboxylic acid (H3 BTC) and flexible N-donor linker 1, 3-bis(2-methylimidazolyl)propane generated two new metal-organic frameworks (MOFs), [ Zn7 (μ3 -OH)2 (BTC)4 (bmp)2 (H2 O)4 ·2H2 O·2DMF] n (1 ) and [Zn(BTC) (Hbmp)·H2 O] n (2 ). 1 has a pentanuclear [Zn5 (μ3 -OH)2 ] subunit, which is further connected by the BTC ligands to shape a layer. The 2D layer is further bridged by BTC and monuclear metal to form a 3D framework. The 3D zinc-BTC substructure has 1D open channels filled by bmp ligands. Polymer 2 shows a 4-connected 3D cds network. While a variation of bmp was imported into the zinc-btc system yielding a two different topological networks, demonstrating that the ligand salt type has an apparent effect in the building of the final networks. Their photochemical properties were measured. Graphical abstract: Two new Zn(II) based supramolecular MOFs synthesized and their photocatalytic properties explored against the photodegradation of methyl violet. Image 1 Highlights: The difference in topologies in both MOFs attributed to conformational flexibility of ligands. These MOFs used as possible photocatalyst for the photodegradation of aromatic dye methyl violet. The plausible photocatalytic mechanism was addressed.